PERSONALITY TRAITS: ANALYSIS OF MAIN CHARACTER IN CINDERELLA MOVIE 2015 BY DISNEY - Okania Mentari; Wennyta Wennyta (Universitas Batanghari Jambi, 2019)
This research used qualitative research. The researcher used personality traits teory to analysis main character in Cinderella movie. After watching movie and read the script, the reseacher concludes four points from five points of personality traits that areoppeness, conscientiousness, extraversion, agreeableness of Cinderella as main character in the movie. That are likes to meet the new people, independent, humble, friendly, enthusiastic, keep the spirit, loving, care, seccumb, helpful, forgiving. It can be concluded that Cinderella is only classified into four types out of five, and it is explained by the behavior and dialogue in Cinderlla movie. It is suggested tofor the future researchers who are interested in deeperstudying about character and characterization of the movie especially on the similar movie. The future researchers can use this research as a reference.